Functional programming paradigm with scheme programming language / Jamal Othman - Othman, Jamal (Unit Penerbitan JSKM, 2024)
Functional programming (FP) is a paradigm which the expression is written in declarative style or bind the expression as mathematical function. FP treats functions as data. Basically, this paradigm was introduced for mathematical computation. Anything that can be computed by the FP than it is considered as computable. Currently, this paradigm has been introduced as an elective or optional course to the students at the tertiary level of education. Other than FP paradigms, the students are also introduced with the structured, object-oriented, logic and scripting paradigms. The main purpose of introducing varieties of programming paradigms is to make sure that the students are able to choose appropriate programming language related to their project scopes and domain. The FP paradigms focus on what is the expected result the program should produce rather than on how the result will be get as applied in structured and object-oriented programming paradigms. This article will discuss details on the characteristics, example of codes which uses the Scheme programming language and implementation of the FP paradigms in the real life.